2021
DOI: 10.1371/journal.pone.0244971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal nutrient restriction during the periconceptional period on placental development in the mouse

Abstract: Maternal undernutrition has detrimental effects on fetal development and adult health. Total caloric restriction during early pregnancy followed by adequate nutrition for the remainder of gestation, is particularly linked to cardiovascular and metabolic disease risks during adulthood. The placenta is responsible for transport of nutrients from the maternal to fetal circulation, and the efficiency with which it does so can be adjusted to the maternal nutrient supply. There is evidence that placental adaptations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…However, in mice a 25% reduction in maternal caloric intake from mid-gestation can result in increased Slc2a3 expression and glucose transport, but this is associated with a secondary reduction in placental system L transport and fetal growth restriction (Ganguly et al, 2012(Ganguly et al, , 2016. In undernourished mice, there is also a report of placental Slc38a4 expression being less, but fetal weight unchanged compared to normally nourished controls (Van Gronigen Case et al, 2021). Last, findings relying on the expression or abundance of nutrient transporters in sheep have suggested that placental glucose and lipid transport capacity may be increased in early pregnancy by maternal undernutrition, as informed by Slc2a1 and Fatp4 expression levels, respectively, and these may relate to normal fetal growth in the model near term (Ma et al, 2011).…”
Section: Changes In Placental Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in mice a 25% reduction in maternal caloric intake from mid-gestation can result in increased Slc2a3 expression and glucose transport, but this is associated with a secondary reduction in placental system L transport and fetal growth restriction (Ganguly et al, 2012(Ganguly et al, , 2016. In undernourished mice, there is also a report of placental Slc38a4 expression being less, but fetal weight unchanged compared to normally nourished controls (Van Gronigen Case et al, 2021). Last, findings relying on the expression or abundance of nutrient transporters in sheep have suggested that placental glucose and lipid transport capacity may be increased in early pregnancy by maternal undernutrition, as informed by Slc2a1 and Fatp4 expression levels, respectively, and these may relate to normal fetal growth in the model near term (Ma et al, 2011).…”
Section: Changes In Placental Functionmentioning
confidence: 99%
“…For instance, other work has found Igf2 to be stably expressed in the placenta even when there are environmentally mediated changes in placental phenotype with reduced placental perfusion in guinea pigs (Carter et al, 2005), or undernutrition in sheep (McMullen et al, 2005). Further, changes in the placental expression of additional imprinted genes, including Igf2r, H19, Dlk1, Grb10 and Slc38a4, have been reported in different animal models subject to unfavourable gestational environments (Coan et al, 2008(Coan et al, , 2011Cuffe et al, 2014;Lesage et al, 2002;Lin et al, 2012;Sferruzzi-Perri et al, 2013;Van Gronigen Case et al, 2021). Thus, imprinted genes are important for mediating adaptive responses in placental physiology, in response to both developmental and environmental cues.…”
Section: Imprinted Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two frequent models of maternal stress include nutritional stress by high fat diet (HFD) or caloric restriction (CR) ( Cortes-Albornoz et al, 2021 ; Van Gronigen Case et al, 2021 ). These exposures have been linked to behavioral alterations indicative of attention deficit hyperactivity disorder (ADHD), autism spectrum disorders (ASD), anxiety, and depression ( Cortes-Albornoz et al, 2021 ; Wen et al, 2022 ; Castillo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, understanding nutrient-sensitive dysregulation in the placenta may not explain whether, or which, nutrient-related mechanisms drove improper neural tube closure earlier in pregnancy, and thus, may not directly inform preventative efforts for NTDs. However, maternal undernutrition, even when limited to the periconceptional and early gestational periods, can have a lasting impact on placental phenotype 51,468 , and changes in the placenta may reflect earlier environments, thus provide clues of key developmental programming phenomena. For clear ethical reasons, investigation of neural tube closure in the human embryo in vivo is not possible, however, our analysis pipeline could be applied as a first step towards characterising the nutrient-sensitive functions of the human yolk sac (YS).…”
Section: Molecular and Cellular Processes Including Nutrient-sensitiv...mentioning
confidence: 99%